2009
DOI: 10.2174/156652309788488587
|View full text |Cite
|
Sign up to set email alerts
|

Use of Genetically Modified Bacteria to Modulate Adaptive Immunity

Abstract: Infectious diseases caused by virulent bacteria are a significant cause of morbidity and mortality worldwide, especially in developing countries. However, attenuated strains derived from pathogenic bacteria, such as Salmonella, are highly immunogenic and can be used as vaccines to promote immunity against parental pathogenic bacteria strains. Further, they can be genetically manipulated to either express foreign antigens or deliver exogenous DNA, in order to induce immunity against other pathogens or antigens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 147 publications
(236 reference statements)
0
8
1
3
Order By: Relevance
“…However, whereas we and other groups (24-26) did not observe a response against the eukaryotic vector, SLs themselves are immunogenic (58) and are prone to deviating an immune response toward immunosuppression in favor of their survival (59). Although the latter feature is largely circumvented by using a eukaryotic expression vector (23), we noted a slight upregulation of IL-1b, IL-10, and MDSC in SL-fed mice.…”
Section: Discussioncontrasting
confidence: 73%
“…However, whereas we and other groups (24-26) did not observe a response against the eukaryotic vector, SLs themselves are immunogenic (58) and are prone to deviating an immune response toward immunosuppression in favor of their survival (59). Although the latter feature is largely circumvented by using a eukaryotic expression vector (23), we noted a slight upregulation of IL-1b, IL-10, and MDSC in SL-fed mice.…”
Section: Discussioncontrasting
confidence: 73%
“…Because of its importance, several viruses have evolved molecular mechanisms to impair T-cell activation and gain advantage over the host immune response to disseminate within infected tissues. 33,38 Given that DCs play a major role in naive T-cell priming, several pathogens have evolved molecular mechanisms to impair the function of DCs. 10,31,39 A recent study using antigen-specific mouse T cells showed that conventional DCs isolated from hMPVinfected lungs fail to induce the proliferation of pOVAspecific DO11.10 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…An optimal live oral Salmonella vaccine would retain its ability to colonize and invade host lymphoid tissues while remaining completely avirulent [4]. Several Salmonella strains with various modifications have been created in an attempt to balance safety and immunogenicity (see reviews [1, 3, 5]), however, there is a need for improved strains.…”
Section: Introductionmentioning
confidence: 99%